Design of Silicon Photonic Structures for Multi-Site, Multi-Spectral Optogenetics in the Deep Brain - Roya Nazempour; Qianyi Zhang; Changbo Liu; Xing Sheng (IEEE Photonics Journal, 2020)
Micro- and nanoscale photonic structures and devices play important roles in the development of advanced biophotonic systems, in particular, implantable light sources for optogenetic stimulations. In this paper, we numerically investigate silicon (Si) photonics based microprobes that can achieve multi-site, multi-spectral optical excitation in the deep animal brain. On Si substrates, silicon nitride (Si3N4) based planar waveguides can deliver visible light in the deep tissue with low losses, and couple to grating emitters diffracting light in targeted brain regions. In our model, we combine near-field wave optic and far-field ray tracing simulations, showing that the designed photonic structures spectrally split blue, green and red photons into different locations in the tissue. Furthermore, by introducing dual grating components, photons at different wavelengths can be spatially separated at different depths. Therefore, these photonic probes can be used to selectively activate or inhibit specific neurons and nuclei, when expressing various corresponding light sensitive opsins. We anticipate that such device strategies can find wide applications in the design of advanced implantable photonic systems for neuroscience and neuroengineering.